CRISPR-based targeting of DNA methylation in Arabidopsis thaliana by a bacterial CG-specific DNA methyltransferase - Ghoshal, Basudev; Picard, Colette L.; Vong, Brandon; Feng, Suhua; Jacobsen, Steven E. (Proceedings of the National Academy of Sciences - PNAS, 2021)
CRISPR-based targeted modification of epigenetic marks such as DNA cytosine methylation is an important strategy to regulate the expression of genes and their associated phenotypes. Although plants have DNA methylation in all sequence contexts (CG, CHG, CHH, where H = A, T, C), methylation in the symmetric CG context is particularly important for gene silencing and is very efficiently maintained through mitotic and meiotic cell divisions. Tools that can directly add CG methylation to specific loci are therefore highly desirable but are currently lacking in plants. Here we have developed two CRISPR-based CG-specific targeted DNA methylation systems for plants using a variant of the bacterial CG-specific DNA methyltransferase MQ1 with reduced activity but high specificity. We demonstrate that the methylation added by MQ1 is highly target specific and can be heritably maintained in the absence of the effector. These tools should be valuable both in crop engineering and in plant genetic research.